Assessment of Duodenal Intraepithelial Lymphocyte Composition (Lymphogram) for Accurate and Prompt Diagnosis of Celiac Disease in Pediatric Patients. Issue 11 (10th November 2021) - Camarero, Cristina; De Andrés, Ana; García-Hoz, Carlota; Roldán, Belén; Muriel, Alfonso; León, Francisco; Roy, Garbiñe
Abstract : INTRODUCTION: Quantitative and phenotypic analyses of duodenal intraepithelial lymphocytes (IELs) by flow cytometry (IEL lymphogram) confer specificity and enable the diagnosis even in unconventional presentations of celiac disease (CD). To evaluate the validity of the IEL lymphograms in the pediatric population for new insights into their use as biomarkers in the natural history of CD. METHODS: We retrospectively included 1, 211 children (602 with active CD, 92 on a gluten-free diet, 47 with potential CD, and 470 nonceliac controls) who required duodenal biopsies in this study. The cutoff values for IEL subsets were established to calculate the probability of disease according to the lymphogram. RESULTS: A celiac lymphogram (a ≥15% increase in gamma-delta T-cell receptor IELs and a simultaneous ≤6% decrease in CD3 surface-negative [sCD3 − ]) IELs was strongly associated with the diagnosis of active CD, which was present in 89.7% of the confirmed patients. The remaining 10% of the celiac patients had a partial celiac lymphogram (≥15% increase gamma-delta T-cell receptor IELs or ≤6% decrease in sCD3 − IELs), with lower diagnostic certainty. On a gluten-free diet, nearly 20% of the patients were indistinguishable from nonceliac subjects based on the lymphogram. In potential CD, a decrease in sCD3 − IELs was a risk marker of progression to villous atrophy and a diagnosis of active CD. DISCUSSION: If a biopsy is clinically indicated, the IEL lymphogram adds specificity to the histological findings, reducing diagnostic delays and misdiagnoses. The lymphogram is useful for monitoring the natural progression of the disease and predicting the transition from potential celiac to overt CD.